Impact of recent economic problems on mental health in Ireland - Kelly, Brendan D. (Int Psychiatry, 2013)
The effect, if any, of recent economic problems on mental health in the Republic of Ireland is not fully clear. Rates of suicide increased slightly between 2006 and 2011, and there was a notable increase in 2011 itself. Rates of psychiatric admission continued to fall, however, in line with national mental health policy. Use of sedative and tranquilliser medications (but not antidepressants) increased, although use in the Republic of Ireland remains substantially lower than in Northern Ireland. Mean self-rated happiness in Ireland declined steadily and significantly between 2005 and 2012. In 2009, as economic problems deepened, satisfaction with income replaced satisfaction with health as the strongest correlate of happiness in Ireland. By 2011/12, however, none of the traditional correlates of happiness retained an independent association with happiness. Overall, these trends suggest that suicide prevention strategies will be increasingly important for Ireland in future years. Active labour-market programmes to address unemployment may also play an important role in suicide prevention. Rates of mental illness and medication usage in the community merit further study. The solution to declining happiness levels may elude purposive description but this trend is likely to reverse as Ireland’s economic prospects improve.